Depressive Symptoms and Emotional Distress of Transnational Mothers: A Scoping Review - Pineros-Leano, María; Yao, Laura; Yousuf, Aroub; Oliveira, Gabrielle (Frontiers in Psychiatry, 2021)
Background: Female led migration is a recent trend that has been gaining momentum, particularly in Latin America. However, little attention has been given to the psychological consequences of mothers who leave their children in their country of origin and migrate to a host country to work. Therefore, it is important to investigate the mental health status of transnational mothers and to further identify issues for intervention and supportive services. Methods: PubMed, PsycINFO, ERIC, CENTRAL, Scopus, and ScienceDirect databases were searched systematically for peer-reviewed articles published from inception through July 2019. The search included the following terms: migrant, immigrant, transnational, transnational mother, AND mood disorders, depressive symptoms, and depression. Initially, 8,375 studies were identified. After exclusionary criteria were applied, 17 studies were identified and included in the review. Results: We found six quantitative studies that investigated depressive symptoms among transnational mothers. Of these studies, three found a positive association between transnational motherhood and depressive symptoms; three of these articles found a null correlation. A total of eight qualitative studies and two mixed-methods studies were found that addressed depressive symptoms and emotional distress among transnational mothers. The eight qualitative studies identified highlighted the significant emotional distress transnational mothers experience. Lastly, the three mixed-methods studies similarly discussed the emotional hardships faced by transnational mothers. Implications: The studies identified suggest that depressive symptoms and emotional distress are prevalent among transnational mothers. Therefore, public health social workers and other mental health providers need to focus on developing strategies to identify and screen transnational mothers for depressive symptoms.